ANALYSIS THE EFFECTS OF YTTERBIUM RARE EARTH ON THE CORROSION RATE OF SACRIFICIAL ANODE ALUMINIUM IN SEAWATER ENVIRONMENT AT ROOM TEMPERATURE - Nurdiansyah, Faisal; Pribadi, Bima Tegar; Rohmannudin, Tubagus Noor; Kurniawan, Budi Agung (Jurnal Rekayasa Mesin, 2024)
Corrosion is a degradation process on metal that happen naturally. Corrosion is one of the most common problems in the industry, resulting the corrosion prevention much needed to increase the lifetime of a material. One of the methods of corrosion prevention is cathodic protection using a sacrificial anode. This research was conducted to analyze the effect of ytterbium rare earth to the corrosion rate of sacrificial anode aluminium in seawater environment. In this research, the ytterbium rare earth used using variety of 14%, 21%, and 22%. The alloy was made using a casting process with a mini furnace, and was characterized using XRF, XRD, SEM-EDX, and Metallographic Tests. Then an immersion test was carried out for 10 days and a tafel test using the Corrtest tool and the CS Studio5 application. The electrolyte solution used is 3.5% NaCl and SCE as a reference electrode. The results show that as the element Ytterbium(Yb) increases, the grain size becomes smaller and finer. This is because Ytterbium(Yb) has a role as a grain refiner. Based on the results of the corrosion rate calculation, the lowest corrosion rate value was sample B with a Yb percentage of 21%, which had a corrosion rate value of 0.005 mm/year on the tafel test. Whereas for the 10-day immersion test, the lowest corrosion rate value was also obtained from sample B with a Yb percentage of 21%, namely 1.030 mm/year. The addition of the element Ytterbium(Yb) decreases the potential value of the sacrificial anode in seawater at room temperature with 22% Al-Yb alloy which has a potential value of the criterion of -821mV, so that only 22% Al-Yb alloy can protect the cathode.